Gastrointestinal Dysfunction in Genetically Defined Neurodevelopmental Disorders - Davidson, Elizabeth A.; Holingue, Calliope; Jimenez-Gomez, Andres; Dallman, Julia E.; Moshiree, Baharak (Seminars in Neurology, 2023)
Gastrointestinal symptoms are common in most forms of neurodevelopment disorders (NDDs) such as in autism spectrum disorders (ASD). The current patient-reported outcome measures with validated questionnaires used in the general population of children without NDDS cannot be used in the autistic individuals. We explore here the multifactorial pathophysiology of ASD and the role of genetics and the environment in this disease spectrum and focus instead on possible diagnostics that could provide future objective insight into the connection of the gut-brain-microbiome in this disease entity. We provide our own data from both humans and a zebrafish model of ASD called Phelan-McDermid Syndrome. We hope that this review highlights the gaps in our current knowledge on many of these profound NDDs and that it provides a future framework upon which clinicians and researchers can build and network with other interested multidisciplinary specialties.
Keywords: gastrointestinal; autism spectrum disorders; neurodevelopmental disorders; abdominal pain; constipation; transit testing